Gerakan Sosial Berbasis Keagamaan dalam Penolakan Kandang Ayam di Cibetus Padarincang - Ahmad Alimun Ali Musa Firdaus; Nayla Sri Ayudya Pratiwi; Azahra Nur Annisa (JOURNAL SAINS STUDENT RESEARCH, 2026)
Abstract. This study analyzes how religious identity is reconstructed and mobilized by activists in the social movement opposing the construction of a large-scale chicken farm in Cibetus Village, Padarincang, Serang Regency, Banten, with the aim of explaining the role of religion as a moral framework, symbolic resource, and political language in local environmental conflict. Employing a qualitative phenomenological approach, the research focuses on capturing the lived experiences and subjective interpretations of activists who directly accompanied residents affected by environmental pollution, health risks, and criminalization. Data were collected through in-depth interviews with activists from various organizations, observations of religious and protest activities, and analysis of movement documents and media reports. The findings show that religious identity was not the initial cause of resistance but became increasingly central as the conflict escalated and formal political and legal channels were perceived as unresponsive. Religious practices such as pengajian, istighosah, collective prayers, and sermons functioned as spaces of moral reflection and social consolidation, enabling activists to transform environmental and health grievances into narratives of moral injustice, religious obligation, and collective responsibility to protect God’s creation. Through this process, religion provided moral legitimacy for resistance, strengthened solidarity, and helped construct a clear antagonistic boundary between “us” as a community of believers defending life, health, and the environment, and “them” as state and corporate actors associated with capital-oriented development. The study concludes that religious identity operates as a dynamic and contingent discursive resource that not only mobilizes collective action but also challenges dominant development narratives, contributing to a deeper understanding of religion, identity politics, and environmental movements in contemporary Indonesia. Keywords: Religious Identity Mobilization; Social Movements; Environmental Conflict Abstrak. Penelitian ini bertujuan menganalisis bagaimana identitas keagamaan direkonstruksi dan dimobilisasi oleh aktivis dalam gerakan penolakan pembangunan kandang ayam skala besar di Desa Cibetus, Kecamatan Padarincang, Kabupaten Serang, Banten, serta menjelaskan peran agama sebagai kerangka moral, sumber daya simbolik, dan bahasa politik dalam konflik lingkungan di tingkat lokal. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi untuk menangkap pengalaman hidup dan pemaknaan subjektif para aktivis yang terlibat langsung dalam pendampingan warga yang terdampak pencemaran lingkungan, ancaman kesehatan, dan kriminalisasi. Data diperoleh melalui wawancara mendalam dengan aktivis dari berbagai organisasi, observasi terhadap praktik keagamaan dan aksi penolakan, serta analisis dokumen gerakan dan pemberitaan media. Hasil penelitian menunjukkan bahwa identitas keagamaan bukanlah pemicu awal perlawanan, tetapi menjadi semakin sentral seiring eskalasi konflik dan tertutupnya jalur formal politik serta hukum yang dianggap tidak responsif terhadap keluhan warga. Praktik keagamaan seperti pengajian, istighosah, doa bersama, dan ceramah berfungsi sebagai ruang refleksi moral dan konsolidasi sosial yang memungkinkan aktivis mentransformasikan persoalan lingkungan dan kesehatan menjadi narasi ketidakadilan moral, kewajiban keagamaan, dan tanggung jawab kolektif untuk menjaga ciptaan Tuhan. Melalui proses tersebut, agama memberikan legitimasi moral bagi perlawanan, memperkuat solidaritas kolektif, serta membentuk batas antagonistik yang jelas antara “kami” sebagai komunitas warga beriman yang memperjuangkan kehidupan, kesehatan, dan lingkungan, dan “mereka” sebagai negara serta korporasi yang diasosiasikan dengan logika pembangunan berorientasi modal. Penelitian ini menegaskan bahwa identitas keagamaan merupakan sumber daya diskursif yang dinamis dan kontingen dalam mobilisasi gerakan sosial, sekaligus menantang wacana pembangunan dominan dalam konteks Indonesia kontemporer. Kata kunci: Mobilisasi Identitas Agama; Gerakan Sosial; Konflik Lingkungan